Effects of processing conditions on extraction of total saponins from bitter gourd (Momordica charantia L.) and its antimicrobial activity against foodborne pathogens - Salman Aboazra, Hanaa Abdelkarim (2016)
A tropical plant, Momordica charantia L., bitter gourd (BG), subcontinent variety, is widely found in Asian countries. The World Health Organization of the United Nations estimates that every year one in three people worldwide get food poisoning leading to food illness or food diseases from consuming contaminated food. Many researches have reported that saponins in BG fruit have biological potency. Therefore, the need to explore a natural source of antimicrobial for food safety and using it as a natural sanitizer was important. The aim of this study is to examine the antimicrobial effect of hot air dried, spray dried, and extrudates of BG crude extracts against selected foodborne pathogens. Optimization of extraction condition using Response Surface Methodology (RSM) was conducted using solvent type, time, and solid to solvent ratio as independent variables while total saponins measured as a dependent response. Different processing methods includes hot air drying at 45°C, spray drying (90, 120, 147.5, 175 and 200°C), and extrusion (80, 100, and 120°C) were applied to produce BG fruit powder. Optimal crude extracts of samples which contain different amount of total saponins were evaluated for antimicrobial activity against eight foodborne pathogens. The extracts that could inhibit the growth of tested pathogens were used in sanitizing test at different exposure times (5, 10, and 15 min). The results of RSM showed that 0.02 g/ml of solid to solvent ratio, time (75 - 120 min), and solvent type (ethanol) was the optimum extraction condition. Hot air dried and extrudate at temperature of 80°C showed a good retention of total saponins with 103.0, 108.8 mg DE/g DM, respectively, compared to initial content of fresh fruit sample 172.7 mg/g DM. BG fruit powder which contain high total saponins had potential bactericidal activity against the tested food pathogens with less than 10 mg/ml in 24 h. Ethanolic extracts of extrudate at temperature of 80°C and hot air dried samples had inhibited the growth of Klebsiella pneumoniae, Staphylococcus epidermidis, Bacillus cereus, Streptococcus mutans, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa with a minimum inhibitory concentration (MIC) of 0.625 - 5.625 mg/ml. The sample extracts possessed bactericidal and bacteriostatic activities against foodborne bacteria. Based on time-kill curve, it showed time needed to destroy the bacteria was within 4 h, except for P. aeruginosa. In conclusions, different processing method possess different total saponin yields in the dried BG fruit powder could have important bactericidal activity and this study will enhance the attempts of using total saponins compound as a potential natural antibacterial agent in food applications.